Medicare Expenditures Associated With Hospital and Emergency Department Use Among Beneficiaries With Dementia - Laura Coots Daras MS, MA; Zhanlian Feng PhD; Joshua M. Wiener PhD; Yevgeniya Kaganova PhD (SAGE Publishing, 2017)
Understanding expenditure patterns for hospital and emergency department (ED) use among individuals with dementia is crucial to controlling Medicare spending. We analyzed Health and Retirement Study data and Medicare claims, stratified by beneficiaries' residence and proximity to death, to estimate Medicare expenditures for all-cause and potentially avoidable hospitalizations and ED visits. Analysis was limited to the Medicare fee-for-service population age 65 and older. Compared with people without dementia, community residents with dementia had higher average expenditures for hospital and ED services; nursing home residents with dementia had lower average expenditures for all-cause hospitalizations. Decedents with dementia had lower expenditures than those without dementia in the last year of life. Medicare expenditures for individuals with and without dementia vary by residential setting and proximity to death. Results highlight the importance of addressing the needs specific to the population with dementia. There are many initiatives to reduce hospital admissions, but few focus on people with dementia.